(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The practice of integrating listening and speaking in the classroom emanates from a belief that the attainment of proficiency in oral production is associated with listening since learners are plunged into the rich exposure of language input by means of listening tasks. Engaging in meaningful communication puts great demands on grammatical accuracy and vocabulary range. In this regard, listening provides an avenue for coming to good terms with knowledge of language structures, lexical units, phonological awareness and metacognition development. In addition, listening demonstrates overall positive effect on the development of oral production for it allows learners to experience good language models to communicate effectively. The study was designed to explore the influence of listening with a focus on top-down and bottom-up processes on the development of oral production. The present study adopted a quantitative approach and the participants were 45 English as a foreign language (EFL) first-year students. It was found that listening and speaking integrated language activities helped learners arrive at understanding of messages; thus, created the basis for production practice